(untitled) (Polis (Santiago), 2021)
The relationship between work and personal life has become evident during the COVID-19 pandemic: paid work, domestic work, care work, personal and family life coexist in the same space and time. Work flooded home spaces and telecommuting was relocated to the center of the domestic realm. This qualitative research analyzes the experience of female academics working remotely during the pandemic in Chile. Through photo-elucidated interviews with a sample of 15 academics from universities from the north, center and south of Chile, the article addresses university-institutionalized gender neutrality as a structure that deepens inequalities and excludes academic women with caretaking responsibilities. The results show an intensification and extension of the online workday, an overload of reproductive work, simultaneity of tasks, emotional vulnerability and isolation. Yet, for some academics, remote work has also meant greater concentration and work flexibility. The various conditions profoundly affect the remote work experience and personal well-being of female academics, as well as their possibilities for knowledge production and scientific productivity. Given the diversity of realities for remote work during the health crisis, university policies on remote work with a gender perspective are urgently required.